EFEKTIVITAS PEMBINAAN NARAPIDANA BERKAITAN DENGAN TINGKAT RESIDIVIS DI LEMBAGA PEMASYARAKATAN KELAS II PALU - Zahra, Zahra (Katalogis, 2015)
The objective of the research was to identify the prisoner restoration effectiveness in Palu  Prison House, Class II-A and the effect of recidivist restoration in Palu  Prison House, Class II-A. The research questions were (1) how effective the prisoner restoration in Palu  Prison House, Class II-A, was, (2) how effective the prisoner restoration in Palu  Prison House, Class II-A, was. The researcher adopted juridical empirical approach by relating the prevailing legal aspects, law and regulations to real facts in the community. The law that was supposed to be one of instruments to combat crimes has a series of long histories of changes and developments in terms of ‘revenge’ to criminals, change to be an instrument to protect one from others and protection to community against crimes as well as restoration media for prisoners to normally live a life in the community.  A prison is supposed to be the estuary of a criminal justice system assigned by a country to deliver restoration, rehabilitation and protection. Unfortunately, the restoration was sometimes inconsistent with the prevailing standards and regulations, leading to unoptimum results and crime recurrence. The sentences to recidivists by the judges shall be re-engineered in terms of better restoration and imprisonment in consistence with the prevailing principles of imprisonment. However, it was not yet practically exercised.